A review of the relationship between stroke and neutrophil-lymphocyte ratio - Ahmed, Mustaq; Reddy, Dhruvi; Green, Siva Ranganathan (International Journal of Advances in Medicine, 2022)
Neutrophil-lymphocyte ratio (NLR) has been a novel biomarker in the literature over decades to assess systemic inflammation. This easily available and cost-effective marker has shown clinical significance in various disease conditions such as infections, sepsis, malignancies, cardiovascular events and even in SARS-COVID-19 pneumonia. NLR has a major association in ischemic stroke patients. Inflammation is a crucial step in the development of ischemic stroke, with neutrophils and lymphocytes comprising the first line defence mechanism. It has a role in stroke initiation, progression of injury, and recovery. This article showed significant correlation between NLR and stroke patients in terms of days of hospital stay, severity and prognosis. High NLR values were found to be associated with higher risk of stroke, prolonged hospital stay and a worse 3 month mortality rate. NLR can thus be integrated into any clinical practice, having an impact on early diagnosis in many clinical scenarios.